PENGEMBANGAN MEDIA VIDEO ANIMASI BERBANTU FLIPACLIP PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS IV SEKOLAH DASAR - Dany Febryansyah Dany; Wiwik Okta Susilawati Wiwik; Antik Estika Hader Antik (STKIP Subang, 2023)
This research is motivated by the lack of focus on students in understanding the learning material provided by the teacher, so that it has an impact on student learning outcomes. To overcome this problem, interesting learning media is needed so that students become more focused and can understand learning material. The learning media developed by researchers are animated videos for the Pancasila Education subject for class IV elementary schools, especially in unit II constituencies and norms in the surrounding environment. This type of research is Research and Development (R&D) and this development model uses the 4- D development model. 4-D has stages, namely define design, development, and disseminate. The results obtained from the development of animated video media are 87.1% validation results, 87.1% practicality results and 84.6% effectiveness results.